Assessing the democratic value of civil society engagement in the European Union - Hüller, Thorsten; Kohler-Koch, Beate (2008)
Abstract: "The title indicates an empirical question, but the main problems to solve are of a theoretical nature: Only when this preparatory work is done, we can - with the help of a theoretical model - investigate the democratic quality of civil society engagement in the EU empirically. So this paper is mostly on ‘asking the right questions’: First, a normative conception of democracy is outlined, which is in our view appropriate to measure and assess the changing quality of European democratic performance (1). Then the interpretations of civil society and its latent democratic functions are introduced (2). In a next step, different conceptions of the EU and respective roles of civil society involvement are discussed because the potential democratic function of civil society varies with the conceptions of the EU as polity (3). Based on these deliberations we develop an analytical model of the 'civil society-EU democracy' relation and specify the relevant questions in order to measure its de